2022
DOI: 10.3390/jcm11174938
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Semaglutide Use in Patients with Type 2 Diabetes: Results from the SURE Spain Multicentre, Prospective, Observational Study

Abstract: Type 2 diabetes (T2D) is a complex disease for which an individualised treatment approach is recommended. Once-weekly (OW) semaglutide is a glucagon-like peptide-1 receptor agonist approved for the treatment of insufficiently controlled T2D. The aim of this study was to investigate the use of OW semaglutide in adults with T2D in a real-world context. SURE Spain, from the 10-country SURE programme, was a prospective, multicentre, open-label, observational study, approximately 30 weeks in duration. Adults with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
5
6
0
Order By: Relevance
“…12 Glycaemic control was achieved without hypoglycaemia or weight gain, aligning with the 2021 Italian guideline objectives to reduce HbA1c as quickly as possible while minimizing risk to patients. 6,7 The results of the SURE Italy study are consistent with efficacy and safety data from the SUSTAIN RCTs [13][14][15][16][17][18] and the SURE studies in Canada, 22 Denmark/Sweden, 23 Spain, 24 Switzerland 25 and the UK 26 and pooled analyses of these studies, 27 the latter of which showed that OW semaglutide use in routine clinical practice was associated with clinically relevant improvements in glycaemic control (-0.2-to -2.5%-point) and body weight (-2.5 to -5.6 kg) and was well tolerated in a wide range of adults with T2D. Regional, small and retrospective RW observational studies of semaglutide in clinical practice in Italy have shown similar results, [28][29][30][31][32] increasing the body of evidence for the benefits of OW semaglutide treatment in adults with T2D in RW settings.…”
Section: Safetysupporting
confidence: 63%
See 1 more Smart Citation
“…12 Glycaemic control was achieved without hypoglycaemia or weight gain, aligning with the 2021 Italian guideline objectives to reduce HbA1c as quickly as possible while minimizing risk to patients. 6,7 The results of the SURE Italy study are consistent with efficacy and safety data from the SUSTAIN RCTs [13][14][15][16][17][18] and the SURE studies in Canada, 22 Denmark/Sweden, 23 Spain, 24 Switzerland 25 and the UK 26 and pooled analyses of these studies, 27 the latter of which showed that OW semaglutide use in routine clinical practice was associated with clinically relevant improvements in glycaemic control (-0.2-to -2.5%-point) and body weight (-2.5 to -5.6 kg) and was well tolerated in a wide range of adults with T2D. Regional, small and retrospective RW observational studies of semaglutide in clinical practice in Italy have shown similar results, [28][29][30][31][32] increasing the body of evidence for the benefits of OW semaglutide treatment in adults with T2D in RW settings.…”
Section: Safetysupporting
confidence: 63%
“…24.5 IU at baseline), although there were changes in insulin usage (e.g. 21 participants stopping bolus insulin).…”
mentioning
confidence: 99%
“…In total, 11.5% of patients discontinued semaglutide treatment, which was comparable with that observed in other SURE studies. [27][28][29][30][31][32][33][34] A further 22.5% patients were reported as either missing the EOS visit, lost to follow-up or withdrawn from the study. These patients with unknown treatment status at EOS were a likely consequence of the severe impact of COVID-19 on the primary care service in France.…”
Section: Adverse Events and Hypoglycaemiamentioning
confidence: 99%
“…The aim of the programme was to complement the findings of the SUSTAIN RCTs, where semaglutide was compared with a series of comparators, and to provide a more complete understanding of once-weekly semaglutide use in a range of clinical scenarios. [27][28][29][30][31][32][33][34] Here we present findings from the SURE France study, which investigated the use of once-weekly semaglutide in routine clinical practice in a real-world population of adult patients with T2D in France. As T2D duration is known to impact glycaemic response to medications, subgroups based on disease duration were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of new type 2 diabetes pharmacological treatment are covered by three original papers [ 11 , 12 , 13 ]. The Yu-Chuan Kang et al study includes a large population sample and an extended follow-up to evaluate the association between dipeptidyl peptidase-4 inhibitors and diabetic retinopathy [ 13 ].…”
mentioning
confidence: 99%